Diabetes in COVID-19: Management - Shruti Brahmbhatt1 *, Vihang Brahmbhatt2, Maulin Mehta3 , Tejas Shah4 (Institute of Medico-legal Publications Pvt Ltd, 2021)
The COVID-19 (Corona Virus Disease-19) has become the most critical health problem worldwide. It wasfirst started from Wuhan, China and now it has affected more than 230 countries and millions of people.The diabetic patients with uncontrolled glycemic state for long term can result in many microvascular andmacrovascular complications. Hence they are most commonly affected individuals during COVID-19. Inthis review we have briefed about the impact of COVID-19 in diabetes, the different pathophysioloy andmanagement of diabetes in this phase.